Recent Approaches for Solid Dose Vaccine Delivery - Nishat Jahan; Sabrina Rahman Archie; Abdullah Al Shoyaib; Nadia Kabir; Karmen Cheung (MDPI AG, 2019)
Recent studies on vaccine delivery systems are exploring the possibility of replacing liquid vaccines with solid dose vaccines due to the many advantages that solid dose vaccines can offer. These include the prospect of a needle-free vaccine delivery system leading to better patient compliance, cold chain storage, less-trained vaccinators and fewer chances for needle stick injury hazards. Some studies also indicate that vaccines in a solid dosage form can result in a higher level of immunogenicity compared to the liquid form, thus providing a dose-sparing effect. This review outlines the different approaches in solid vaccine delivery using various routes of administration including, oral, pulmonary, intranasal, buccal, sublingual, and transdermal routes. The various techniques and their current advancements will provide a knowledge base for future work to be carried out in this arena.